The Effect of Shear Force on Skin Viability in Patients with Type 2 Diabetes - Luuk A. de Wert; Margot Geerts; Sander van der Brug; Laura Adriaansen; Martijn Poeze; Nicolaas Schaper; Nicole D. Bouvy (Journal of Diabetes Research)
Background. Shear is a major risk factor in the development of diabetic foot ulcers, but its effect on the skin of patients with type 2 diabetes mellitus (DM) remains to be elucidated. The aim was to determine skin responses to shear in DM patients with and without diabetic polyneuropathy (DNP). Methods. The forearm skin was loaded with 14.5 N shear (+2.4 kPa pressure) and with 3.5 kPa pressure for 30 minutes in 10 type 2 DM patients without DNP, 10 type 2 DM patients with DNP, and 10 healthy participants. A Sebutape collected IL-1α (measure of tissue damage). A laser Doppler flowmeter measured cutaneous blood cell flux (CBF) as a measure of the reactive hyperaemic skin response. Findings. Reactive hyperaemia and IL-1α release was significantly increased after shear loading in all three groups and was higher compared to the responses to pressure loading. The reactive hyperaemic response after shear loading was impaired in patients with type 2 DM compared to healthy participants but did not differ between patients with and without DNP. The reactive hyperaemic response was negatively correlated with the blood glucose level but did not correlate with the DNP severity score. Interpretation. Shear is important in the development of tissue damage, but the reparative responses to shear are impaired in patients with type 2 DM. DNP was not associated with altered skin responses, suggesting that the loss of protective sensation to sense shear to skin remains a key factor in the development of diabetic foot ulcers in patients with DNP.